2012
DOI: 10.1186/1758-2555-4-45
|View full text |Cite
|
Sign up to set email alerts
|

Coordinative variability and overuse injury

Abstract: Overuse injuries are generally defined as a repetitive micro-trauma to tissue. Many researchers have associated particular biomechanical parameters as an indicator of such injuries. However, while these parameters have been reported in single studies, in many instances, it has been difficult to verify these parameters as causative to the injury. We have investigated overuse injuries, such as patella-femoral pain syndrome, using a dynamical systems approach. Using such methods, the importance of the structure o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
247
1
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 285 publications
(256 citation statements)
references
References 39 publications
5
247
1
3
Order By: Relevance
“…The authors further concluded that this increase in the in-phase relationship resulted from an increase in pelvis frontal plane ROM. Although the technique utilised to assess coordination and variability should be based on the question asked in the study (Hamill et al, 2012) the use of CRP limits the analysis of coordination to the phase relationship between two segments. On the other hand, vector coding and the proposed four coordination phases (Chang et al, 2008) provides an additional insight to the dominancy of one segment over another and this can offer more valuable information in a clinical setting (Seay et al, 2011).…”
Section: Q5mentioning
confidence: 99%
“…The authors further concluded that this increase in the in-phase relationship resulted from an increase in pelvis frontal plane ROM. Although the technique utilised to assess coordination and variability should be based on the question asked in the study (Hamill et al, 2012) the use of CRP limits the analysis of coordination to the phase relationship between two segments. On the other hand, vector coding and the proposed four coordination phases (Chang et al, 2008) provides an additional insight to the dominancy of one segment over another and this can offer more valuable information in a clinical setting (Seay et al, 2011).…”
Section: Q5mentioning
confidence: 99%
“…In most research in motor control, variability is traditionally equated with noise, detrimental to system performance and is typically eliminated from data as a source of error [4,5]. Techniques for reducing and eliminating both within-and between-participants variability have been used.…”
Section: Introductionmentioning
confidence: 99%
“…VARelements above the upper limit implies that the motor system is too unstable and noisy, whereas VARelements below the lower limit indicates the system is too stereotypical, less likely to exhibit exploratory behaviour, and thus less capable of adapting to perturbations ) and more likely to overload specific tissues (Hamill, 2012). However, it is unclear what magnitude of VARelements should be deemed optimal, and at what point VARelements crosses an upper or lower limit to become too much or too little, respectively.…”
Section: Balance Between Positive and Negative Effects Of Varelementsmentioning
confidence: 96%
“…lateral epicondylalgia) with chronic musculoskeletal pain (Bartlett et al 2007;Hamill et al 2012). This interpretation is consistent with the variability-overuse hypothesis (Wheat, 2005;Bartlett et al 2007) and loss of complexity hypothesis (Lipsitz et al 2002;Hamill et al 2012), which suggest that injury will emerge once the reduction of VARelements reaches a critical threshold/limit.…”
Section: Negative Consequences Of Reduced Variability In Chronic Painmentioning
confidence: 99%